The effectiveness of the training process of skiers using computer vision methods - Novikova N.B. ,; Novikov A.N. ,; Ivanova I.G. ,; Belyova A.N. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to experimentally validate the use of computer vision techniques to enhance the efficiency of ski racing training management. Methods and structure of the study. The examination of video footage of athletes gliding on roller skis at their top speed was conducted using a specially designed software that incorporates a motion-detection system for athletes, powered by the Alpha Pose neural network. Results and conclusions. The advanced software enables precise identification of ski racers' movements in training and competition settings, providing visual representation of angular features and velocities in joints. Additionally, it can generate videograms automatically. The data obtained can be used to assess the effectiveness of skiing techniques and detect technical flaws that may go unnoticed using conventional methods.